Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar IPAS Kelas IV SDN 1 Banyuripan - Indana Zulfa Wahyu Utami; Sri Suwartini; Putri Zudhah Ferryka (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
Concerns over suboptimal IPAS achievement among fourth-grade elementary school students, reflected in limited conceptual mastery and insufficient engagement during instruction, prompted an examination of the effectiveness of the Problem Based Learning (PBL) model. The study applied a quantitative approach within a quasi-experimental framework, utilizing a pretest-posttest control group design. A total of 44 students participated, distributed into an experimental group and a control group. Learning outcome tests were used to gather data, which were subsequently processed through normality and homogeneity tests, followed by paired sample t-test and independent sample t-test analyses. The findings demonstrated a statistically significant difference between groups, with a significance value of 0.000 < 0.05, indicating greater improvement in the experimental class. In addition, the experimental group achieved a higher posttest mean score compared to the control group, while the N-Gain score for the experimental class fell within the moderately effective category. These results confirm that the implementation of the PBL model contributes positively to improving IPAS learning outcomes. Accordingly, PBL may be considered an appropriate instructional alternative for fostering more active student involvement and strengthening conceptual understanding in the learning process.